The rotation of primary starter culture mixtures results in batch-to-batch variations during Gouda cheese production - Decadt, Hannes; Weckx, Stefan; De Vuyst, Luc (Frontiers in Microbiology, 2023)
Industrial production of Gouda cheeses mostly relies on a rotated use of different mixed-strain lactic acid bacteria starter cultures to avoid phage infections. However, it is unknown how the application of these different starter culture mixtures affect the organoleptic properties of the final cheeses. Therefore, the present study assessed the impact of three different starter culture mixtures on the batch-to-batch variations among Gouda cheeses from 23 different batch productions in the same dairy company. Both the cores and rinds of all these cheeses were investigated after 36, 45, 75, and 100 weeks of ripening by metagenetics based on high-throughput full-length 16S rRNA gene sequencing accompanied with an amplicon sequence variant (ASV) approach as well as metabolite target analysis of non-volatile and volatile organic compounds. Up to 75 weeks of ripening, the acidifying Lactococcus cremoris and Lactococcus lactis were the most abundant bacterial species in the cheese cores. The relative abundance of Leuconostoc pseudomesenteroides was significantly different for each starter culture mixture. This impacted the concentrations of some key metabolites, such as acetoin produced from citrate, and the relative abundance of non-starter lactic acid bacteria (NSLAB). Cheeses with the least Leuc. pseudomesenteroides contained more NSLAB, such as Lacticaseibacillus paracasei that was taken over by Tetragenococcus halophilus and Loigolactobacillus rennini upon ripening time. Taken together, the results indicated a minor role of leuconostocs in aroma formation but a major impact on the growth of NSLAB. The relative abundance of T. halophilus (high) and Loil. rennini (low) increased with ripening time from rind to core, Two main ASV clusters of T. halophilus could be distinguished, which were differently correlated with some metabolites, both beneficial (regarding aroma formation) and undesirable ones (biogenic amines). A well-chosen T. halophilus strain could be a candidate adjunct culture for Gouda cheese production.